Influence of Co and B12 on the growth and nitrogen fixation of Trichodesmium - Rodriguez, Irene B.; Ho, Tung-Yuan (Frontiers in Microbiology, 2015)
We investigated the influence of varying cobalt (Co) and B12 concentrations to growth and nitrogen fixation of Trichodesmium, a major diazotroph in the tropical and subtropical oligotrophic ocean. Here we show that sufficient inorganic Co, 20 pmol L-1, sustains the growth of Trichodesmium either with or without an additional B12 supply. We also found that in these culture conditions, nitrogen levels fixed by Trichodesmium were higher in treatments with insufficient B12 than in treatments with higher B12 availability. Under limited inorganic Co availability, ranging from 0.2 to 2 pmol L-1, Trichodesmium growth was significantly compromised in cultures without B12. In these low Co concentrations, addition of 400 pmol L-1 of B12 supported phytoplankton growth indicating that B12 supply augmented for the low Co concentrations. Our study demonstrates that Trichodesmium has an absolute Co requirement, which is not replaceable with Zn, and that B12 supply alleviates stress in cases where Co is limiting. These results show that the interlocking availabilities of Co and B12 may influence the growth and nitrogen fixation of Trichodesmium in the ocean.